Dôvodová správa k zákonu č. 59/1999 Z.z., ktorým sa mení a dopĺňa zákon č. 229/1995 Z.z. ...
Dôvodová správa k zákonu č. 59/1999 Z.z., ktorým sa mení a dopĺňa zákon č. 229/1995 Z.z. o spotrebnej dani z liehu.